1993
DOI: 10.1007/bf00196966
|View full text |Cite
|
Sign up to set email alerts
|

Changes in composition of the outer epidermal cell wall of pea stems during auxin-induced growth

Abstract: The gross composition of the outer epidermal cell wall from third internodes of Pisum sativum L. cv. Alaska grown in dim red light, and the effect of auxin on that composition, was investigated using interference microscopy. Pea outer epidermal walls contain as much cellulose as typical secondary walls, but the proportion of pectin to hemicellulose resembles that found in primary walls. The pectin and hemicellulose fractions from epidermal peels, which are enriched for outer epidermal wall but contain internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Bret-Harte et al (1991) found that in the absence of exogenous sugar, IAA depresses deposition of material into the pea outer epidermal wall. The primary reason for the low deposition rate is that under these conditions IAA causes a massive loss of hemicellulose from the outer wall (Bret-Harte and Talbott 1993). The primary reason for the low deposition rate is that under these conditions IAA causes a massive loss of hemicellulose from the outer wall (Bret-Harte and Talbott 1993).…”
Section: Relationship Of These Results To Epidermal Control Of Elongamentioning
confidence: 99%
See 2 more Smart Citations
“…Bret-Harte et al (1991) found that in the absence of exogenous sugar, IAA depresses deposition of material into the pea outer epidermal wall. The primary reason for the low deposition rate is that under these conditions IAA causes a massive loss of hemicellulose from the outer wall (Bret-Harte and Talbott 1993). The primary reason for the low deposition rate is that under these conditions IAA causes a massive loss of hemicellulose from the outer wall (Bret-Harte and Talbott 1993).…”
Section: Relationship Of These Results To Epidermal Control Of Elongamentioning
confidence: 99%
“…The primary reason for the low deposition rate is that under these conditions IAA causes a massive loss of hemicellulose from the outer wall (Bret-Harte and Talbott 1993). The gross composition of epidermal peels does not indicate a loss of hemicellulose from the cell walls with auxin treatment, and in fact the composition of epidermal peels is rather different than that reported for the outer wall (Bret-Harte and Talbott 1993). The gross composition of epidermal peels does not indicate a loss of hemicellulose from the cell walls with auxin treatment, and in fact the composition of epidermal peels is rather different than that reported for the outer wall (Bret-Harte and Talbott 1993).…”
Section: Relationship Of These Results To Epidermal Control Of Elongamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the significant number of studies on cell wall composition and analysis, isolation and further analysis of the OEW is not trivial. Microscopic analysis of the OEW of pea stems showed higher cellulose content than typical primary walls (Bret-Harte and Talbott, 1993). Isolation of the polysaccharide fraction of mature tomato fruit cuticles showed an equimolecular contribution of the three main components of cell wall: cellulose, hemicellulose, and pectin (López-Casado et al, 2007).…”
Section: The Discontinuous Construction Of the Cutinized Cell Wallmentioning
confidence: 93%
“…The epidermis is considered one of the factors affecting the rate of growth in plants by restraining expansion of the internal tissues (Taiz, 1984 ;Kutschera, 1992 ;Bret-Harte and Talbott, 1993).…”
Section: Introductionmentioning
confidence: 99%